Lithium cobalt oxide positive electrode material with O3 structure as well as low-temperature preparation method and application of lithium cobalt oxide positive electrode material

By preparing O3 structure lithium cobalt oxide positive electrode material under low temperature conditions, the problems of material structure failure and poor electrochemical performance caused by high temperature treatment are solved, and the efficient, stable and low-cost preparation of the material is achieved.

CN119911980APending Publication Date: 2025-05-02XI AN JIAOTONG UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510118461.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art deals with long-term materials at high temperatures, resulting in problems such as damage to the structure of materials, poor electrochemical properties and cycle stability.

Method used

The low-temperature preparation method is adopted, including solid-phase calcination at 450-550 °C to prepare sodium-containing layered oxide NaxCoO2, then mix it uniformly with the lithium source, and perform ion exchange treatment at 100-300 °C. After filtration, washing and drying, LixCoO2, the positive electrode layered oxide material of O3-structured lithium-ion battery is prepared.

Benefits of technology

It significantly improves the material's tap density, thermal stability and other physical properties, avoids crystal defects and lattice distortion caused by high-temperature calcination, improves the structural stability and electrochemical properties of the material, and reduces energy consumption and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911980A_ABST
    Figure CN119911980A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium cobalt oxide positive electrode material with an O3 structure as well as a low-temperature preparation method and application thereof, and belongs to the technical field of preparation of positive electrode materials of lithium ion batteries. The preparation method comprises the following steps: by adopting a method of combining low-temperature solid-phase calcination with low-temperature Li < + > / Na < + > ion exchange, firstly calcining and synthesizing a sodium-containing layered oxide (NaxCoO2) under a relatively low-temperature condition, then uniformly mixing the sodium-containing layered oxide (NaxCoO2) with a lithium source, carrying out low-temperature solid-phase or liquid-phase ion exchange treatment, and filtering, washing and drying to obtain the O3 structure layered oxide (LiCoO2). According to the method disclosed by the invention, the thermodynamically stable O3-phase lithium cobalt oxide layered oxide can be prepared under a low-temperature condition, the prepared oxide particles consist of micron-sized particles, the grain size distribution is 1-10 microns, the grain size is controllable, the consistency is good, and the method is suitable for a voltage range of 4.3-4.7 V and can be widely applied to the electronic product and power automobile market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery positive electrode material preparation, and specifically relates to an O3 structure lithium cobalt oxide positive electrode material and a low-temperature preparation method and application thereof. Background Art

[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, low self-discharge rate and fast response speed, have shown the strongest development trend in the field of electrochemical energy storage, and can effectively solve the intermittent and instability problems of renewable energy and improve energy efficiency. Among the many components of lithium-ion batteries, the quality of the positive electrode material directly affects whether lithium-ion batteries can meet the diverse market needs, and is related to the breadth and depth of lithium-ion battery applications in the field of new energy.

[0003] Different positive electrode materials have different properties. Lithium iron phosphate (LiFePO4) has low cost and high thermal stability, but its energy density is relatively low and its low-temperature performance is poor. Ternary materials (such as nickel cobalt manganese oxide NCM and nickel cobalt aluminum oxide NCA) have good overall performance and can take into account both energy density and cycle life, but their rate performance and stability under high voltage are poor. Lithium cobalt oxide (LiCoO2) has high energy density and high voltage platform, excellent rate performance, and can fully meet the pursuit of lightweight, long battery life, and fast charging of portable electronic devices. Although lithium cobalt oxide has problems such as high cost and scarce cobalt resources, as the earliest commercialized lithium-ion battery positive electrode material, lithium cobalt oxide has a mature production process and stable quality control, and high-voltage lithium cobalt oxide technology is constantly developing. Its energy density and electrochemical performance can be further improved through modification, and it still maintains significant advantages in specific scenarios such as the high-end consumer electronics field.

[0004] The synthesis of traditional O3-type lithium cobalt oxide materials usually requires long-term sintering for more than 10 hours at a calcination temperature of 700℃-900℃ or even higher. For example, the invention patent with publication number CN 114956210 A discloses a single-crystal lithium-ion battery positive electrode material with different layered structures and its preparation method and application, which is calcined at 700-900℃ for 6-20 hours after co-precipitation treatment. The high-temperature and long-term calcination process has high energy consumption, high safety risks, high production costs, and low production efficiency. In addition, long-term treatment at high temperature may cause the crystal structure of the material to be distorted, and defects such as stress and dislocations are generated inside the lattice, destroying the original layered structure, thereby affecting the crystallinity and phase stability of the material. It may also cause the surface structure of the material to be destroyed, resulting in surface cracks, increased pores, and other problems, resulting in more side reactions on the electrode surface, further deteriorating the electrochemical performance and cycle stability of the material. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an O3 structure lithium cobalt oxide positive electrode material and a low-temperature preparation method and application thereof, so as to solve the technical problems of the prior art that long-term treatment at high temperature leads to material structure destruction, poor electrochemical performance and cycle stability.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a low-temperature preparation method of an O3 structure lithium cobalt oxide positive electrode material, comprising: solid phase calcination at 450-550°C to prepare a sodium-containing layered oxide Na x CoO2, then evenly mix it with a lithium source, perform ion exchange treatment at 100°C~300°C, and then filter, wash and dry to obtain the O3 structure lithium ion battery positive electrode layered oxide material Li x CoO2; where 0.60≤ x ≤1.00.

[0007] Preferably, the low-temperature preparation method of the above-mentioned O3 structure lithium cobalt oxide positive electrode material comprises the following steps: 1) According to the chemical formula Na x CoO2, 0.60 ≤ x ≤1.00, take sodium source and cobalt source, mix and grind them evenly, calcine at 450-550 °C for 0.5-2 h, and cool naturally to room temperature to obtain O3' and P3' type sodium ion battery layered oxide Na x CoO2; 2) Layered oxide Na x CoO2 and lithium source are mixed, ion exchange treatment is carried out at 100℃~300℃ for 0.5~3h, and then filtered, washed and dried to obtain O3 type lithium ion battery positive electrode layered oxide material Li x CoO2.

[0008] Preferably, in step 1), the sodium source is Na2CO3, Na2O2 or NaOH; and the cobalt source is Co3O4, Co2O3 or CoCO3.

[0009] Preferably, in step 1), the sintering system is: starting from room temperature, heating to 450-550° C. at a heating rate of 1-5° C. / min and calcining for 0.5-2 h.

[0010] Further preferably, in step 2), the lithium source is Li2CO3, LiNO3, LiCl, LiOH·H2O or LiCH3COO; the sodium ion battery layered oxide Na x Na in CoO2 + Li +The molar ratio is 1:(1~10).

[0011] More preferably, the solid phase ion exchange treatment is to convert the sodium ion battery layered oxide Na x CoO2 and solid lithium source are dry mixed evenly; liquid phase ion exchange treatment is to convert the layered oxide Na x CoO2 and a lithium source solution with a concentration of 0.5 to 10 mol / L are stirred evenly.

[0012] Preferably, the solvent of the liquid phase ion exchange lithium source solution comprises water and ethanol; the sodium ion battery layered oxide Na x The dosage ratio of CoO2 to lithium source solution is 1:5~1:200 mg / μL.

[0013] The invention also discloses an O3 structure lithium cobalt oxide positive electrode material prepared by the above low-temperature preparation method. The O3 structure lithium cobalt oxide positive electrode material is composed of micron-sized particles, and the grain size is uniformly distributed between 1 and 10 μm.

[0014] Preferably, the O3 structure lithium cobalt oxide positive electrode material is suitable for a wide voltage range of 4.3 to 4.7V.

[0015] The invention also discloses the application of the above-mentioned O3 structure lithium cobalt oxide positive electrode material in the preparation of lithium ion batteries.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the O3 structure lithium cobalt oxide positive electrode material disclosed in the present invention adopts low temperature calcination combined with low temperature Li + / Na + In the ion exchange method, the raw materials are first dry-mixed and then calcined at a relatively low temperature to produce sodium-containing layered oxide NaCoO2, which is then fully mixed with a lithium source and Li + / Na + After ion exchange treatment, filtration, washing and drying, O3-type layered oxide LiCoO2 is obtained. The preparation of sodium-containing layered oxide adopts a fully dry mixed raw material source for calcination, which can significantly improve the tap density, thermal stability and other physical properties of the material. The equipment relied on is simple and universal, and the process is stable and reliable. The low-temperature calcination conditions are mild and easy to control, which can avoid crystal defects and lattice distortion caused by high-temperature calcination to a certain extent, and is conducive to the orderly growth of the crystal structure and the uniform distribution of particle size, thereby improving the structural stability of the material; low-temperature calcination has strong operability, high safety, can greatly reduce energy consumption and production costs, improve production efficiency, and is suitable for large-scale industrial production. Li O3-type lithium cobalt oxide positive electrode material + / Na +Ion exchange treatment can be carried out through two pathways: solid phase and liquid phase. The solid phase pathway does not require additional auxiliary solvents, has a simple process and high stability; the liquid phase pathway has highly controllable reaction conditions, fast ion diffusion rate, uniform and efficient exchange. Both pathways can achieve controllable ion exchange under low temperature conditions, have relatively mild equipment requirements, high process safety factor, energy saving, emission reduction, cost reduction and efficiency improvement, and have outstanding advantages in large-scale industrial production.

[0017] The O3 structure lithium cobalt oxide positive electrode material prepared by the new preparation process disclosed in the present invention has basically the same electrochemical properties as the material prepared by the traditional process, is suitable for a voltage range of 4.3 to 4.7 V, has a stable and reliable material structure, uniform particle distribution, controllable particle size, and good batch uniformity, and can be widely used in the electronic products and power vehicle markets. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The O3'-type sodium ion battery layered oxide Na prepared in Example 1 of the present invention 0.84 X-ray diffraction spectrum of CoO2; Figure 2 The X-ray diffraction spectrum of the O3-type lithium cobalt oxide layered positive electrode material LiCoO2 prepared in Example 1 of the present invention; Figure 3 The O3'-type sodium ion battery layered oxide Na prepared in Example 2 of the present invention 0.6 SEM image of CoO2; Figure 4 The first charge and discharge curve of the O3-type lithium cobalt oxide layered positive electrode material LiCoO2 prepared in Example 2 of the present invention at 3.0-4.7V and 1C; Figure 5 The sodium ion battery layered oxide Na of the mixed structure of O3' and P3' prepared in Example 3 of the present invention 0.76 X-ray diffraction spectrum of CoO2; Figure 6 This is a scanning electron microscope image of the O3-type lithium cobalt oxide layered positive electrode material LiCoO2 prepared in Example 3 of the present invention; Figure 7 The first charge-discharge curve of the O3-type lithium cobalt oxide layered positive electrode material LiCoO2 prepared in Example 4 of the present invention at 3.0-4.55V and 0.1C; Figure 8 The rate performance of the O3-type lithium cobalt oxide layered positive electrode material LiCoO2 prepared in Example 5 of the present invention at 3.0-4.65V. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0020] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0021] The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1 In this embodiment, according to the precursor chemical formula Na 0.84 CoO2 ingredients.

[0022] A method for preparing an O3 structure LiCoO2 positive electrode material comprises the following steps: Step 1. Low temperature solid phase calcination: According to the chemical formula Na 0.84 CoO2 ingredients, the molar ratio of sodium and cobalt elements is 0.84:1.0, the corresponding Na2O2 and Co3O4 are weighed respectively, placed in a ball mill and mixed evenly, and then placed in a muffle furnace, heated to 550℃ in an air atmosphere at a heating rate of 3℃ / min and calcined for 1h, and naturally cooled to room temperature to obtain O3'-type sodium ion battery layered oxide Na 0.84 CoO2; Step 2. Solid phase ion exchange: According to nNa + :nLi + =1:10 molar ratio, weigh the O3' type sodium ion battery layered oxide Na obtained in step 1 0.84CoO2 and Li2CO3 are mixed evenly in a ball mill and then placed in a muffle furnace for solid phase ion exchange treatment at a low temperature of 300°C for 2 hours. They are then centrifuged and washed three times with deionized water. The product obtained by drying and collecting is the O3 type lithium ion battery positive electrode layered oxide LiCoO2.

[0023] The charging and discharging performance test process of the positive electrode material prepared in this embodiment is as follows: A certain amount of the positive electrode material prepared in this embodiment, acetylene black, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1:1, added to N-methylpyrrolidone (NMP) to prepare a slurry, wherein the content of NMP is 30 times that of PVDF, and evenly coated on an aluminum foil. The slurry was vacuum dried at 80° C. for 12 hours, and then cut into pole pieces with a diameter of 12 mm using a mold; a metal lithium sheet was used as a negative electrode, a Celgard 2400 commercial polypropylene film was used as a separator, and an electrolyte was LP30. The slurry was assembled into a button cell of model CR2032 in a glove box filled with inert gas.

[0024] The O3 type lithium ion layered oxide elements prepared in this embodiment are evenly distributed in the grains, and the particle size is about 5 μm. 0.84 XRD of CoO2 Figure 1 From the XRD pattern, it can be seen that all diffraction peaks belong to the O3'-type layered structure; the XRD pattern of the prepared positive electrode material LiCoO2 is shown Figure 2 From the XRD diagram, we can see that all the diffraction peaks belong to the O3 type layered structure.

[0025] Example 2 In this embodiment, according to the precursor chemical formula Na 0.6 CoO2 ingredients.

[0026] A method for preparing an O3 structure LiCoO2 positive electrode material comprises the following steps: Step 1. Low temperature solid phase calcination: According to the chemical formula Na 0.6 CoO2 ingredients, the molar ratio of sodium and cobalt elements is 0.6:1.0, the corresponding Na2CO3 and CoCO3 are weighed respectively, placed in a ball mill and mixed evenly, and then placed in a muffle furnace, heated to 450℃ in an air atmosphere at a heating rate of 1℃ / min and calcined for 0.5h, and naturally cooled to room temperature to obtain the sodium ion battery layered oxide NaO3' structure. 0.6 CoO2; Step 2. Solid phase ion exchange: According to nNa + :nLi + =1:8 molar ratio, weigh the O3' structure sodium ion battery layered oxide Na obtained in step 10.6 CoO2 and LiNO3 are mixed evenly in a ball mill and then placed in a muffle furnace for solid phase ion exchange treatment at a low temperature of 270°C for 2 hours. They are then centrifuged and washed three times with deionized water. The product obtained by drying and collecting is the O3 type lithium ion battery positive electrode layered oxide LiCoO2.

[0027] The morphology of the O3' structure precursor prepared in this example is shown in Figure 3 From the figure, we can see that the O3' structure precursor particles are mainly agglomerated spherical, evenly distributed, and the particle size is about 8 μm.

[0028] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the first charge and discharge capacities of the O3 structure lithium cobalt oxide positive electrode material prepared in this example at a voltage range of 3.0 to 4.7 V and 1C are 233.32 mAh / g and 213.02 mAh / g, respectively. Figure 4 .

[0029] Example 3 In this embodiment, according to the precursor chemical formula Na 0.76 CoO2 ingredients.

[0030] A method for preparing an O3 structure LiCoO2 positive electrode material comprises the following steps: Step 1. Low temperature solid phase calcination: According to the chemical formula Na 0.76 CoO2 ingredients, the molar ratio of sodium and cobalt elements is 0.76:1.0, the corresponding NaOH and Co2O3 are weighed respectively, placed in a ball mill and mixed evenly, and then placed in a muffle furnace, heated to 500℃ in an air atmosphere at a heating rate of 5℃ / min and calcined for 2h, and naturally cooled to room temperature to obtain a sodium ion battery layered oxide Na with a mixed structure of O3' and P3' 0.76 CoO2; Step 2. Solid phase ion exchange: According to nNa + :nLi + =1:4 molar ratio, weigh the sodium ion battery layered oxide Na with mixed structure of O3' and P3' obtained in step 1 0.76 CoO2 and LiCH3COO are mixed evenly in a ball mill and then placed in a muffle furnace for solid phase ion exchange treatment at a low temperature of 250°C for 3 hours. They are then centrifuged and washed three times with deionized water. The product obtained by drying and collecting is the O3 type lithium ion battery positive electrode layered oxide LiCoO2.

[0031] The layered oxide Na of the sodium ion battery with mixed structure of O3' and P3' prepared in this example 0.76 XRD of CoO2 Figure 5 The morphology of the O3 structure lithium cobalt oxide positive electrode material prepared in this embodiment is shown in Figure 6 From the figure, we can see that the particles are mainly in the shape of agglomerated spheres with a particle size of about 2 μm.

[0032] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the first charge and discharge capacities of the O3 structured positive electrode material prepared in this example are 220.85 mAh / g and 204.41 mAh / g at a voltage range of 3.0 to 4.6 V and 0.1 C, respectively.

[0033] Example 4 In this embodiment, the ingredients are prepared according to the precursor chemical formula NaCoO2.

[0034] A method for preparing an O3 structure LiCoO2 positive electrode material comprises the following steps: Step 1. Low temperature solid phase calcination: According to the chemical formula NaCoO2, the molar ratio of sodium to cobalt is 1.0:1.0. The corresponding Na2O2 and Co3O4 are weighed respectively, mixed evenly in a ball mill, and then placed in a muffle furnace. The mixture is heated to 550°C at a heating rate of 3°C / min in an air atmosphere and calcined for 1h. The mixture is naturally cooled to room temperature to obtain O3'-type sodium ion battery layered oxide NaCoO2. Step 2. Liquid phase ion exchange: The O3'-type sodium ion battery layered oxide NaCoO2 prepared in step 1 is immersed in a 0.5 mol / L LiOH·H2O aqueous solution, and stirred evenly in a ratio of 1:200 mg / μL of the sodium ion layered oxide to the LiOH·H2O aqueous solution. The mixture is subjected to liquid phase ion exchange treatment at a low temperature of 100°C for 3 hours, followed by centrifugation and washing with deionized water for 2 to 3 times. The product obtained by drying and collecting is the O3-type lithium ion battery positive electrode layered oxide material LiCoO2.

[0035] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the first charge and discharge capacities of the O3 structured cathode material prepared in this example are 217.67 mAh / g and 193.01 mAh / g, respectively, at a voltage range of 3.0 to 4.55 V and a rate of 0.1 C. Figure 7 shown.

[0036] Example 5 In this embodiment, according to the precursor chemical formula Na 0.96 CoO2 ingredients.

[0037] A method for preparing an O3 structure LiCoO2 positive electrode material comprises the following steps: Step 1. Low temperature solid phase calcination: According to the chemical formula Na 0.96 CoO2 ingredients, the molar ratio of sodium and cobalt elements is 0.96:1.0, the corresponding Na2CO3 and CoCO3 are weighed respectively, placed in a ball mill and mixed evenly, and then placed in a muffle furnace, heated to 450℃ in an air atmosphere at a heating rate of 1℃ / min and calcined for 0.5h, and naturally cooled to room temperature to obtain the sodium ion battery layered oxide NaO3' structure. 0.96 CoO2; Step 2. Liquid phase ion exchange: The O3'-type sodium ion battery layered oxide Na prepared in step 1 0.96 CoO2 was immersed in a 10 mol / L LiCl ethanol solution, stirred evenly in a ratio of 1:5 mg / μL of sodium ion layered oxide and LiCl ethanol solution, and subjected to liquid phase ion exchange treatment at a low temperature of 150°C for 0.5h, followed by centrifugation and washing twice with anhydrous ethanol. The product obtained by drying and collecting is the O3 type lithium ion battery positive electrode layered oxide material LiCoO2.

[0038] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the rate performance of the O3 structure lithium ion layered positive electrode material prepared in this example at 3.0-4.65V is Figure 8 .

[0039] In summary, the present invention can realize the preparation of thermodynamically stable O3-type lithium cobalt oxide positive electrode materials at lower temperatures and in shorter time, while reducing production costs and energy consumption and improving production efficiency, which is of great significance for the industrial production of electric vehicles and consumer electronic products. The above experiments have verified that the method of the present invention can prepare thermodynamically stable O3-phase lithium cobalt oxide layered oxides under low temperature conditions. The prepared oxide particles are all composed of micron-sized particles, with a grain size distribution between 1 and 10 microns, controllable particle size, good consistency, and suitable for a voltage range of 4.3 to 4.7V, and can be widely used in the electronic products and power vehicle markets.

[0040] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A low-temperature preparation method for an O3 structure lithium cobalt oxide positive electrode material, characterized in that: include: Preparation of sodium-containing layered oxide Na by solid phase calcination at 450-550 °C x CoO2, then evenly mix it with a lithium source, perform ion exchange treatment at 100°C~300°C, and then filter, wash and dry to obtain the O3 structure lithium ion battery positive electrode layered oxide material Li x CoO2; where 0.60≤ x ≤1.

00.

2. The low-temperature preparation method of the O3 structure lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The following steps are involved: 1) According to the chemical formula Na x CoO2, 0.60 ≤ x ≤1.00, take sodium source and cobalt source, mix and grind them evenly, calcine at 450-550 °C for 0.5-2 h, and cool naturally to room temperature to obtain O3' and P3' type sodium ion battery layered oxide Na x CoO2; 2) Layered oxide Na x CoO2 and lithium source are mixed, ion exchange treatment is carried out at 100℃~300℃ for 0.5~3h, and then filtered, washed and dried to obtain O3 type lithium ion battery positive electrode layered oxide material Li x CoO2.

3. The low-temperature preparation method of the O3 structure lithium cobalt oxide positive electrode material according to claim 2, characterized in that: In step 1), the sodium source is Na2CO3, Na2O2 or NaOH; the cobalt source is Co3O4, Co2O3 or CoCO3.

4. The low-temperature preparation method of the O3 structure lithium cobalt oxide positive electrode material according to claim 2, characterized in that: In step 1), the sintering system is: starting from room temperature, heating to 450-550°C at a heating rate of 1-5°C / min and calcining for 0.5-2h.

5. The low-temperature preparation method of the O3 structure lithium cobalt oxide positive electrode material according to claim 4, characterized in that: In step 2), the lithium source is Li2CO3, LiNO3, LiCl, LiOH·H2O or LiCH3COO; the sodium ion battery layered oxide Na x Na in CoO2 + Li + The molar ratio is 1:(1~10).

6. The low-temperature preparation method of the O3 structure lithium cobalt oxide positive electrode material according to claim 5, characterized in that: Solid phase ion exchange treatment is to convert the sodium ion battery layered oxide Na x CoO2 and solid lithium source are dry mixed evenly; liquid phase ion exchange treatment is to convert the layered oxide Na x CoO2 and a lithium source solution with a concentration of 0.5 to 10 mol / L are stirred evenly.

7. The low-temperature preparation method of the O3 structure lithium cobalt oxide positive electrode material according to claim 6, characterized in that: The solvent of the liquid phase ion exchange lithium source solution includes water and ethanol; the sodium ion battery layered oxide Na x The dosage ratio of CoO2 to lithium source solution is 1:5~1:200 mg / μL.

8. The O3 structured lithium cobalt oxide positive electrode material prepared by the low temperature preparation method according to any one of claims 1 to 7, characterized in that: The O3 structure lithium cobalt oxide positive electrode material is composed of micron-sized particles, and the grain size is evenly distributed between 1 and 10 μm.

9. The O3 structured lithium cobalt oxide positive electrode material according to claim 8, characterized in that: The O3 structure lithium cobalt oxide positive electrode material is suitable for a wide voltage range of 4.3 to 4.7V.

10. Use of the O3 structure lithium cobalt oxide positive electrode material according to claim 8 or 9 in the preparation of lithium ion batteries.

Citation Information

Cited By

  • Lithium cobalt oxide composite material, preparation method, positive plate and lithium ion battery

    CN121149182A